Pembiayaan Sindikasi Bank Syariah Perspektif Hukum Ekonomi Syariah: Syndicated Financing of Sharia Banks from the Perspective of Sharia Economic Law - Aditya Ramadhaniar El Islamy; Nana Herdiana Abdurrahman; Yoyok Prasetyo (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
From the standpoint of Islamic Economic Law, this article seeks to describe and examine the syndicated financing of Islamic Banks in Indonesia. With the kind of library research used to examine the formulation of the problem in this study, a qualitative research methodology was used to conduct this study. The findings of this study suggest that a hybrid contract or multi-contract approach can be used to implement Islamic banking product innovation. Sharia syndicated finance products exist in banking as a result of the requirement for huge quantities of funding, which means that Islamic banks must work with other banks since they will not be able to support it alone. In accordance with the Fatwa DSN No: 91/DSN-MUI/IV/2014, syndicate financing is permitted. Musyarakah Mutanaqishah contracts are typically used for syndicated financing in Islamic banks. The Sharia Banking Law, KHES, Fatwa DSN, and other relevant rules have both been accommodated by syndicated financing in Islamic banks. The Sharia Supervisory Board will continue to oversee the implementation of syndicated financing products at Indonesian Islamic Banks so that it is, in theory, consistent with Sharia Economic Law and no restrictions are broken.